NCOG-24. WAKE FOREST NCORP RESEARCH BASE FEASIBILITY STUDY OF RAMIPRIL FOR PREVENTING COGNITIVE DECLINE IN GLIOBLASTOMA PATIENTS RECEIVING BRAIN RADIOTHERAPY (WF-1801). (9th November 2020) - Cramer, Christina; Page, Brandi; Wefel, Jeffrey S; Dressler, Emily; Ip, Edward; Rapp, Steve; Shaw, Edward; Weaver, Kathryn; Lesser, Glenn; Chan, Michael
Abstract: INTRODUCTION: Chronic neuro-inflammation after brain radiotherapy (RT) contributes to radiation-induced cognitive decline (RICD). The renin angiotensin system (RAS) may mediate this inflammatory cascade after RT. Ramipril is an angiotensin-converting enzyme inhibitor used to treat hypertension and has good blood-brain barrier penetration. By blocking RAS activation, ramipril reduces neuro-inflammation and preclinical data show that ramipril administration during RT can prevent RICD. METHODS: WF-1801 is an ongoing feasibility study that will enroll a total of 75 patients. Patients ≥ 18 with newly diagnosed and pathologically confirmed GBM who will receive chemoradiation are eligible. All participants take ramipril daily during RT and for 4 months thereafter. Ramipril is titrated from 1.25mg to 5mg daily over 3 weeks. A cognitive battery that includes the Hopkins Verbal Learning Test-Revised (HVLT-R), Trail Making Test (TMT), and Controlled Oral Word Association test (COWA) is administered at baseline, end of RT, and 1-month and 4-months post-RT. The co-primary endpoints are retention rate (with retention defined as compliance with > 75% of drug therapy doses) and neurocognitive function at 1-month post-RT. To estimate the effect of ramipril on cognitive function, performance on the cognitive battery will be compared to a historical control (cognitive data from the control arm of RTOG 0825). ApoE genotyping is being performed as a correlative study. RESULTS: 31 of a planned 75 participants have been enrolled over 14 months. 20 of 31 (64.5%) are male. 21 (67.7%) are between the age of 40-64. 20 (95.6%) are white and 29 (93.6%) are not Hispanic or Latino. CONCLUSION: Despite a pause in accrual due to COVID-19, we are easily meeting planned accrual goals. Community oncology-based clinical trials of interventions to prevent cognitive toxicity appear to be feasible. GBM patients seem eager to enroll in studies seeking to prevent cognitive decline. Supported by NCI grant UG1CA189824.